If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(7r + -5) = -141 Reorder the terms: 3(-5 + 7r) = -141 (-5 * 3 + 7r * 3) = -141 (-15 + 21r) = -141 Solving -15 + 21r = -141 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 21r = -141 + 15 Combine like terms: -15 + 15 = 0 0 + 21r = -141 + 15 21r = -141 + 15 Combine like terms: -141 + 15 = -126 21r = -126 Divide each side by '21'. r = -6 Simplifying r = -6
| 3(7r-5)=-141 | | 2(-2)-10=0 | | 2x-5=7x-5+2x | | 3n=48 | | x-10=7x-40 | | -5(1-4x)=8x+23 | | h-5=27 | | 17-3(w+5)=(w+5)-2w | | 51=3(3+2y) | | -4x+(-5x+21)=6 | | 8-5(7g-4)=98 | | 3(1+8r)=-165 | | log(y)=2.7 | | 6y+4=5y-3 | | 7x+4=2x+49 | | 7=(8x+5)+5 | | h+14=63 | | 223+334567.564383= | | r-15=16 | | 3y-10+y+54=8y+50-6y | | 5+2s+7=28 | | 12(80-x)=816 | | 2+5+x=3+4 | | 19-x-5=30 | | (25b-6)-8(3b+3)=-7 | | 8+3(-2n-7)=-(-5-3n) | | (x+4)(3x-24)=0 | | 7(b-5)=72 | | 18+-6g=-12g | | 3px(-3)=36 | | -2(-6x-4)=8x+2(x-2) | | 3(14+-5y)-5y=10 |